2016
DOI: 10.1530/eje-16-0095
|View full text |Cite
|
Sign up to set email alerts
|

Does metabolic health in overweight and obesity persist? – Individual variation and cardiovascular mortality over two decades

Abstract: Objective: Overweight and obese individuals may be metabolically healthy, but attention needs to be given to long-term persistence of this trait and any associated variation in cardiovascular risk. Design: Cross-sectional and longitudinal variation in metabolic health and associated cardiovascular mortality were analysed in 1099 white European-origin normal-weight and overweight or obese males followed for 20 years. Methods: Definitions of metabolic health were based on LDL and HDL cholesterol, triglycerides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The disease risks associated with MHO and MONW vary across studies and across disease outcomes studied. Some studies found that the disease risk for MHO individuals is similar to that of normal‐weight individuals (at least for cardiovascular disease , stroke , peripheral vascular disease , dyslipidemia , type 2 diabetes ) and mortality ), even after many years of follow‐up. However, cumulating evidence from several large‐scale prospective studies suggests that MHO individuals have a higher risk than healthy normal‐weight individuals for many cardiometabolic outcomes (cardiovascular disease , cerebrovascular disease , hypertension , insulin resistance and type 2 diabetes ), yet their risk is lower than that of metabolically unhealthy obese individuals.…”
Section: Disease Risk Associated With Mho and Monwmentioning
confidence: 99%
See 3 more Smart Citations
“…The disease risks associated with MHO and MONW vary across studies and across disease outcomes studied. Some studies found that the disease risk for MHO individuals is similar to that of normal‐weight individuals (at least for cardiovascular disease , stroke , peripheral vascular disease , dyslipidemia , type 2 diabetes ) and mortality ), even after many years of follow‐up. However, cumulating evidence from several large‐scale prospective studies suggests that MHO individuals have a higher risk than healthy normal‐weight individuals for many cardiometabolic outcomes (cardiovascular disease , cerebrovascular disease , hypertension , insulin resistance and type 2 diabetes ), yet their risk is lower than that of metabolically unhealthy obese individuals.…”
Section: Disease Risk Associated With Mho and Monwmentioning
confidence: 99%
“…Lifestyle and demographic factors have been shown to explain at least part of the difference between metabolically healthy and metabolically unhealthy obese individuals. MHO individuals are generally younger, female, more often of African ancestry, have a relatively lower BMI and waist circumference, tend to live a healthier lifestyle (smoke less, more physically active, healthier diet) and have less often a family history of cardiometabolic disease compared to their unhealthy obese peers . Similar factors partially explain why some normal‐weight individuals are metabolically unhealthy; that is, MONW individuals are often older, male, less likely of African ancestry, have a higher BMI and larger waist circumference, live a less healthy lifestyle and have more often a family history of cardiometabolic disease compared to healthy normal‐weight individuals .…”
Section: Factors Contributing To Mho and Monwmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, MHO adults are at an increased risk for developing T2DM than NWMH adults. In another study, Kaur and colleagues investigated whether metabolic health persists in overweight and obese individuals long term. They studied 1099 NW, overweight, or obese male individuals (mean age 46.4 years) for 20 years.…”
Section: Obesity As a Risk Factor For Hypertension And Coronary Heartmentioning
confidence: 99%